1986
DOI: 10.1093/nar/14.2.721
|View full text |Cite
|
Sign up to set email alerts
|

Structure of gene and pseudogenes of human apoferritin H

Abstract: Ferritin is composed of two subunits, H and L. cDNA's coding for these proteins from human liver (1,2,3), lymphocytes (4) and from the monocyte-like cell line U937 (5) have been cloned and sequenced. Southern blot analysis on total human DNA reveals that there are many DNA segments hybridizing to the apoferritin H and L cDNA probes (1,2,4,6). In view of the tissue heterogeneity of ferritin molecules (7,8), it appeared possible that apoferritin molecules could be coded by a family of genes differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 40 publications
(25 reference statements)
3
64
1
Order By: Relevance
“…21 Interestingly, ferritin in cancer cells consists mainly of heavy chains. 22,23 Others have suggested that there is another species of ferritin in cancer cells called super-heavy chain or P43. 24 In the present studies, we sought to characterize the nature of ferritin in melanoma cells and to investigate its possible effects on immune responses.…”
mentioning
confidence: 99%
“…21 Interestingly, ferritin in cancer cells consists mainly of heavy chains. 22,23 Others have suggested that there is another species of ferritin in cancer cells called super-heavy chain or P43. 24 In the present studies, we sought to characterize the nature of ferritin in melanoma cells and to investigate its possible effects on immune responses.…”
mentioning
confidence: 99%
“…Standardization was with respect to 28s and 18s rRNAs as well as by control hybridization with a human a-actin cDNA probe (pHM-aPX, kindly provided by Patrick Lemaire, EMBL, Heidelberg). The cDNA probes for individual genes were: pal-5 for al-antitrypsin [36]; pHL 1423 for human lysozyme; pHIL1-P for IL-1p (kindly provided by C. Schneider, ICGEB, Trieste, Italy) ; pha2ml for human a2-macroglobulin (kindly provided by G. Bell, Chiron, Emmeryville, USA) [37]; pFB for complement factor B (gift of D. Campbell, Oxford, UK); FRL600 for ferritin light chain [38] and FR36 for ferritin heavy chain [39] (gifts of F. Costanzo, Naples, Italy); IL-6 (IFNP2) cDNA [40] was a gift of Dr P. Seghal (Rockfeller University, New York, NY). The probes were 32P-labeled according to Feinberg and Vogelstein [41].…”
Section: Rna Extraction and Northern Blot Analysismentioning
confidence: 99%
“…1) and human H gene (6) contain a modest excess of G-C bases, 64% and 72%, respectively. Upstream of the TATAA box is a 29-bp sequence (-65 to -38), of which 27 bases are conserved in the human H-flanking region (6), and the last 6 are also found in the chicken H gene (33). In the rat (Fig.…”
Section: Spiomentioning
confidence: 99%
“…However, the isolation of genomic copies encoding the human H subunit (6,7) and human and rat L subunits (8,9) has demonstrated the presence of several processed pseudogenes. In addition,…”
mentioning
confidence: 99%
See 1 more Smart Citation